THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER TRUST THROUGH VARIABLES INTERVENING CUSTOMER SATISFACTION USING STRUCTURAL EQUATION MODELING METHOD IN PT.XYZ - Sari, Santika; Almaidani, Adella Nurha; Nurfajriah, Nurfajriah; Zaman, Akhmad Nidhomuz (Teknik Industri Unikom, 2021)
In companies engaged in the service sector, of course it cannot be separated from consumers, the need for food and customer satisfaction. Customer satisfaction at PT. PT. XYZis also the orientation of the company. However, in this newly established company, there are no orders that satisfy customers, so they can assess what factors cause customer satisfaction and what factors or things can be related to Customer Satisfaction. The things that have an influence on service quality are customer trust and reliability of service quality. Using structural equation modeling methods can make it easier to see the value or influence between variables. From this result, it can help evaluation if the three variables have a positive or good effect. Then the company needs to make a strategy to increase customer satisfaction. The results of this study found that the involvement of service quality has a positive and significant effect on customer satisfaction because the higher the involvement of service quality obtained, the higher the level of customer satisfaction in the company. In addition, it is also concluded that service quality and customer satisfaction are correlated so that it has a positive influence on customer trust.